Regionalization of Soil and Water Conservation Aimed at Ecosystem Services Improvement - Hu, Xiaoqian; Li, Zhongwu; Nie, Xiaodong; Wang, Danyang; Huang, Jinquan; Deng, Chuxiong; Shi, Lin; Wang, Lingxia; Ning, Ke (Scientific reports, 2020)
To effectively control soil erosion, three hierarchies of the National Soil and Water Conservation Regionalization Scheme have been established in China. However, the scheme has its limits, which can be summarized by two points: first, the tertiary hierarchy functional region exhibits obvious heterogeneity; second, the ecosystem function does not influence the regionalization scheme results during the process of regionalization. To enhance the guidance of the regionalization, a new indicator system included soil erosion risk, soil erosion intensity and ecosystem service value was developed to explore the subdivision of the tertiary hierarchy functional region. Moreover a scheme for the subdivision of the tertiary hierarchy functional region was formed. In this scheme, the central Hunan hilly soil conservation and living environmental protection section was divided into three subregions: Luoxiao-Xuefeng Mountain high ecological value section, Xiangjiang middle and downstream medium ecological value section, and Hengyang Basin low ecological value section. Specifically, with regard to soil and water conservation regionalization, the concept of subregions within the tertiary hierarchy-based functional region was proposed and the new indicator system that highlighted ecosystem functions was applied for the first time on a regional scales; this method provides a new way of thinking about other regionalization schemes.